Faktor-Faktor yang Mempengaruhi Produksi Sagu (Metroxylon SP) di Kabupaten Konawe Selatan - Tamtama, Ary; Akhmad; Irma Sribianti; Mohammad Natsir (Agrisurya, 2024)
Sago, a versatile food source with industrial applications, holds significant economic value in Southeast Sulawesi. This study investigates the factors affecting sago) production in South Konawe Selatan Regency. Fieldwork conducted from July to October 2023 surveyed 34 sago processors across three sub-districts: Konda, Wolasi, and West Ranomeeto. The Cobb-Douglas production function served as the analytical model. The results reveal a positive and statistically significant influence of processed raw material quantity, labor input, fuel consumption, and water usage on sago aci production. Interestingly, processing experience did not demonstrate a statistically significant impact. These findings offer valuable insights for optimizing sago aci production in the region.